'Listen and learn:' participant input in program planning for a low-income urban population at cardiovascular risk - Rachel S. Kirzner; Inga Robbins; Meghan Privitello; Marianne Miserandino (BMC, 2021)
Abstract Background Poverty increases the risk of cardiac disease, while diminishing the resources available to mitigate that risk. Available prevention programs often require resources that low-income residents of urban areas do not possess, e.g. membership fees, resources to purchase healthy foods, and safe places for physical activity. The aim of this study is to obtain participant input in order to understand the health-related goals, barriers, and strengths as part of planning a program to reduce cardiovascular risk. Methods In a mixed methods study, we used written surveys and focus groups as part of planning an intervention specifically designed to meet the needs of lower income individuals. Based on prior research, we used Self-Determination Theory (SDT) and its core constructs of autonomy, competence, and relatedness as the theoretical framework for analysis. The study collected information on the perspectives of low-income urban residents on their risks of cardiovascular disease, their barriers to and supports for addressing health needs, and how they addressed barriers and utilized supports. Focus group transcripts were analyzed using standard qualitative methods including paired coding and development of themes from identified codes. Results Participants had health goals that aligned with accepted approaches to reducing their cardiovascular risks, however they lacked the resources to reach those goals. We found a lack of support for the three SDT core constructs. The barriers that participants reported suggested that these basic psychological needs were often thwarted by their environments. Conclusions Substantial disparities in both access to health-promoting resources and in support for autonomy, competence, and relatedness must be addressed in order to design an effective intervention for a low-income population at cardiac risk.